Sistem Informasi Penjualan Ikan di UD. Karya Jaya Berbasis Web Menggunakan PHP dan MySQL - Moh Rofiki; Achmad Baijuri; Muhammad Ali Ridla (Institut Informatika dan Bisnis Darmajaya, 2023)
Due to the fact that fish have multiple paths to the final consumer, the impact on the price of fish to the final consumer increases with the length of the path, different sales channels in fish marketing have different prices for each channel. Fish Auction (TPI) is one of the main fisheries operations, and is an important component that drives fishermen's business and welfare. Before using the internet to sell fish at UD. Karya Jaya consumers still come directly to the warehouse to buy fish, it is not uncommon for consumers to be disappointed because the fish they want to buy has run out. The system that runs on UD. Karyajaya is currently still manual so buyers still come directly to the warehouse, so the number of existing buyers and customers is also limited. The solution proposed to overcome the problem at UD. Library research is carried out using the library research method, which is a research procedure that produces data in the form of writing or speech as well as individual behavior that is observed in certain situations and studied from a whole, comprehensive, and holistic perspective. When all system functionality runs smoothly, it can be concluded that the system built can provide information on fish availability and make it easier for the local community or people from across the island to make fish purchase transactions at UD. By Jaya Masalembu. Keywords : Information System; Sale; TPI